Development of liquid whey-based yoghurt beverage: A case of whey-to-milk ratios and types of stabilizers - Fibrianto, Kiki; Pratama, Fam, Immanuel Evan; Wulan, Siti Narsito (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The high volume of whey from cheese production in dairy industries has not been optimally utilized. However, cheese whey possesses high nutritional value, offering potential as raw material for yoghurt drink. This research studied the effect of whey-to-milk ratio (i.e., 50:50, 65:35, and 75:25) and stabilizer type (i.e., high methoxyl pectin, carboxymethyl cellulose, and iota carrageenan) on the physicochemical and sensory characteristics of whey-based yoghurt beverages. Physicochemical analysis covered five parameters (i.e., titratable acidity, pH, total solid, viscosity, and syneresis) using a Factorial Randomized Complete Block Design (RCBD) with three replications. Data were processed using ANOVA and Tukey’s post-hoc test (α = 0.05). For sensory analysis, whey-based yoghurt beverage was compared with a control (100% milk treatment) and two commercial products. Sensory evaluation was performed on 158 panelists using rate-all-that-apply and 5 points scale hedonic for 10 attributes (i.e., color, visual thickness, milky aroma, yoghurt aroma, sweetness, sourness, mouthfeel thickness, creaminess, astringency, and overall acceptability). Data were analyzed using Kruskal-Wallis and Mann-Whitney (α = 0.05). Whey:milk ratio significantly affected titratable acidity, total solid (TS), viscosity, and syneresis. Meanwhile, stabilizer type significantly influenced viscosity and syneresis. The combination of a 50:50 whey:milk ratio and iota carrageenan produced the best formulation based on the Multiple Attribute Zeleny method. In conclusion, the whey-based drinking yoghurt demonstrates overall consumer acceptability comparable to both commercial and control products, indicating promising market potential.